Samoa : Detailed Assessment of Compliance with the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2007)
This Detailed Assessment of Compliance with the Basel Core Principles for Samoa highlights general preconditions for effective banking supervision. The Central Bank of Samoa (CBS) should consider introducing some straightforward specific capital charges for market price risk and foreign exchange risk. The CBS should require banks to have in place mechanisms for regularly valuing collateral and assessing the strength of guarantees. Several recommendations to further improve the regulatory role of the CBS in accordance with current international standards have been noted and future efforts shall focus on incorporating and developing these as appropriate.